Substitutability and Protectionism : Latin America's Trade Policy and Imports from China and India - Facchini, Giovanni; Olarreaga, Marcelo; Silva, Peri; Willmann, Gerald (World Bank, Washington, DC, 2012)
The authors examine the trade policy response of Latin American governments to the rapid growth of China and India in world markets. To explain higher protection in sectors where a large share is imported from these countries, they extend the "protection for sale" model to allow for different degrees of substitutability between domestically produced and imported varieties. The extension suggests that higher levels of protection toward Chinese goods can be explained by high substitutability between domestically produced goods and Chinese goods, whereas lower levels of protection toward goods imported from India can be explained by low substitutability with domestically produced goods. The data support the extension to the "protection for sale" model, which performs better than the original specification in terms of explaining Latin America's structure of protection.